Further Research on Insulation Coordination of UHV Half-Wavelength Power Transmission Line - Liuchun ZHANG (Zhongguo dianli)
Ultra high voltage half wavelength transmission (UHV HWACT) is a kind of transmission mode with large capacity and long distance, which has the advantages that it is not necessary to install reactive compensation devices of the line and to build switch substations, and will be widely used in China. Research results on insulation coordination will be the base of UHV HWACT technique applied to engineering construction. Firstly, this paper determined the continuous operating voltage, the rated voltage and the absorbed energy of the UHV HWACT lightning arrester; secondly, the line insulator configuration was determined by the design method of polluted external insulation, and the air gap distance was also determined; finally, research on insulation coordination was also carried out when considering power fluctuation.